Erosion characteristics of N720/alumina oxide/oxide ceramic matrix composites in a combustion environment. Issue 8 (July 2022) - Panakarajupally, Ragav P.; Mirza, Farhan; El Rassi, Joseph; Morscher, Gregory N.; Abdi, Frank; Choi, Sung
Abstract: The erosion behavior of N720/Alumina oxide/oxide composite was investigated under a combustion environment to better represent particle ingestion of a jet engine. The effect of particle velocity, particle size, temperature and impingement angle were investigated. In addition, room temperature studies were also conducted for comparison. Eroded sites were investigated using optical and scanning electron microscopy to understand the extent of erosion and erosion mechanisms. The results indicate that erosion rate increased with an increase in particle velocity and particle size. Also, erosion rate increased from room temperature to 815 °C and then decreased from 815 °C to 1200 °C. Brittle fracture is the predominant mode under normal impacts and as the impact angle is decreased increased ploughing/wear is evident.